Пусть Х - первое число, тогда второе 1,2Х. Составим уравнение:
(Х + 1,2Х) : 2 = 9,46
2,2Х : 2 = 9,46
2,2Х = 9,46 * 2
2,2Х = 18,92
Х = 18,92 : 2,2
Х = 8,6 - первое число
1,2 * 8,6 = 10,32 - второе число
проверяем
(8,6 + 10,32) : 2 = 9,46
1+1,2=2,2 части сумма чисел
18,92:2,2=8,6 меньшее число
8,6*1,2=10,32 большее число
Пусть Х - первое число, тогда второе 1,2Х. Составим уравнение:
(Х + 1,2Х) : 2 = 9,46
2,2Х : 2 = 9,46
2,2Х = 9,46 * 2
2,2Х = 18,92
Х = 18,92 : 2,2
Х = 8,6 - первое число
1,2 * 8,6 = 10,32 - второе число
проверяем
(8,6 + 10,32) : 2 = 9,46